The Influence of Social Media About Covid-19 on Handwashing Behavior, Mask Wearing and Physical Distancing of Indonesian Students - Erika Martining Wardani; Difran Nobel Bistara; Eppy Setiyowati (Universitas STRADA Indonesia, 2020)
Efforts to prevent the spread of covid-19 through social media by providing information about covid-19. The study aims to determine the effect of social media on covid19 on hand washing behavior, mask wearing and physical distancing among Indonesian students. A pre-experimental research method with pre-test and post-test design. The research sample was 5400 students who were taken using simple random sampling technique. Health education interventions are given through social media and then the data is collected by distributing questionnaires with google form. Data were analyzed using the Wilcoxon test. The results showed that after intervention through social media about covid-19 there was a change in transmission prevention behavior (p value 0.046), hand washing behavior (p value 0.011), mask wearing (p value 0.014), and physical distancing (p value 0.000). Social media is effectively used to provide health education because it can increase student knowledge and influence behavior in preventing covid-19 transmission